2012
DOI: 10.1016/j.ygyno.2011.11.043
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of oral or intrauterine device-delivered progestin in patients with complex endometrial hyperplasia with atypia or early endometrial adenocarcinoma: A meta-analysis and systematic review of the literature

Abstract: There is a lack of high quality evidence for the efficacy of progestin in CAH or EC. The available evidence however suggests that treatment with oral or intrauterine progestin is similarly effective. The risk of progression during treatment is small but longer follow-up is required. Evidence from prospective controlled clinical trials is warranted to establish how the efficacy of progestin for the treatment of CAH and EC can be improved further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(104 citation statements)
references
References 60 publications
3
99
1
1
Order By: Relevance
“…However, this was for inoperable cases caused by medical morbidity and not for fertility-sparing therapy [80]. According to a recent review, 17 of 37 patients with stage IA (without myometrial invasion), grade 1 endometrial cancer achieved a complete response with a progestin-containing intrauterine device with a pooled complete response rate of 46% (95% confidence interval, 29%-63%) [78], which is a somewhat disappointing outcome. Hence, some investigators have reported the outcomes of a combined use of progestincontaining intrauterine device with oral progestin [18] or gonadotropin-releasing hormone agonist [17] for fertilitysparing therapy to achieve better outcomes than either agent alone.…”
Section: Oncologic Outcomes After Progestin Therapymentioning
confidence: 99%
“…However, this was for inoperable cases caused by medical morbidity and not for fertility-sparing therapy [80]. According to a recent review, 17 of 37 patients with stage IA (without myometrial invasion), grade 1 endometrial cancer achieved a complete response with a progestin-containing intrauterine device with a pooled complete response rate of 46% (95% confidence interval, 29%-63%) [78], which is a somewhat disappointing outcome. Hence, some investigators have reported the outcomes of a combined use of progestincontaining intrauterine device with oral progestin [18] or gonadotropin-releasing hormone agonist [17] for fertilitysparing therapy to achieve better outcomes than either agent alone.…”
Section: Oncologic Outcomes After Progestin Therapymentioning
confidence: 99%
“…A systematic review found a pooled regression rate of 90% for AH treated with LNG-IUS 14/20 μg levonorgestrel/24 hours and a dose-dependent increase in response rate when oral progestin was compared to LNG-IUS (26). Mean time taken to achieve complete response for patients with AH and early EC on different progestin therapy regimens was 5.9 months (range=1-12 months) in a meta-analysis (27). Whether the progestin dose delivered to the endometrium by the LNG-IUS Jaydess is too low to overcome high-risk endometrial hyperplasia or if the short duration of therapy (3-6 weeks) is explanatory for the low response rate in women with high-risk endometrial hyperplasia in our study remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Post-treatment sampling of the endometrium reveals CAH regression in up to 100% of cases, and carcinoma regression in up to 70%. 10 Because of atrophy that is induced by progestin, sampling may be difficult. In the current case, a resectoscope was used to obtain tissue after initial therapy.…”
Section: Discussionmentioning
confidence: 99%